Dynamics of Lithospheric Overturns and Implications for Venus's Surface. Issue 11 (8th November 2020) - Uppalapati, S.; Rolf, T.; Crameri, F.; Werner, S. C.
Abstract: Venus is currently characterized by stagnant‐lid mantle convection, but could have previously experienced episodes of global resurfacing due to lithospheric overturn. Using numerical models of Venus's interior, we attempt to explain Venus's surface characteristics in the context of interior evolution and to understand how Venus's tectonic history has diverged from Earth's. For both the stagnant‐ and the episodic‐lid regime, we explore the role of reference mantle viscosity; for the latter regime, we also explore the role of the lithospheric yield stress. Our stagnant‐lid models predict thicker crust and younger surface than typically inferred from cratering statistics. When considering resurfacing episodes, the yield stress influences the frequency of overturns, which limits crustal thickness to better agree with previous independent estimates. Surface age is variable and depends on overturn frequency and resurfacing rate between overturns but reaches larger values just before an upcoming overturn event compared to values in the stagnant‐lid cases. Both regimes predict substantial lateral variations in surface age, instead of an end‐member uniform surface age indicating the cessation time of the last overturn, because ongoing volcanic resurfacing is spatially heterogeneous and dominates over tectonic resurfacing. Reviewing the crater‐based surface age variations suggests that the model‐predicted age spreads in the episodic scenario could be consistent with Venus's cratering record. Moreover, we find that a small fraction of crust can resist recycling during overturns. These outcomes indicate that overturn events may allow for surface age variations that reproduce Venus's surface better than stagnant‐lid models. Plain Language Summary: In contrast to Earth, Venus currently does not feature plate tectonics inhibiting effective crustal recycling into the planetary interior. Yet, its surface features only few and almost randomly distributed craters, which suggests a globally young and more homogeneous surface age than on other planetary surfaces. To date, it remains unclear whether these surface characteristics are generated in an equilibrium style of resurfacing due to volcanism or whether large‐scale tectonic overturns are required to explain the observations. Here, we use numerical models of Venus's interior evolution to predict the planet's surface characteristic like crustal thickness and surface age in two geodynamic regimes, either with or without tectonic overturns. With overturns, predicted mean crustal thickness and mean surface age are closer to other independent estimates. Both regimes predict substantial lateral variations of surface age (which is thus nonuniform), because even if global resurfacing happens at a time, ongoing and spatially heterogeneous volcanism modifies the age distribution subsequently. However, inspection of independent Venus crater‐based surface ages and geological mapping reveals that our predicted variations using an episodic scenario could be consistent with the planet's cratering record. Within our modeling framework, the episodic regime seems thus more promising to explain Venus's surface age characteristics. Key Points: Episodic‐lid models predict thinner crust and older surface than stagnant‐lid models Both stagnant and episodic regime predict substantial lateral variation in surface age Our episodic‐lid model captures Venus's age and crustal characteristics better